De novo assembly of the mitochondrial genome of Glycyrrhiza glabra and identification of two types of homologous recombination configurations caused by repeat sequences - Guowang Zhou; Meiling Qin; Xiuli Liu; Yonghui Qi; Xiaobin Ou; Min Tang (BMC Genomics)
Abstract Background Glycyrrhiza glabra, which is widely used in medicine and therapy, is known as the ‘king of traditional Chinese medicine’. In this study, we successfully assembled and annotated the mitochondrial and chloroplast genomes of G. glabra via high-throughput sequencing technology, combining the advantages of short-read (Illumina) and long-read (Oxford Nanopore) sequencing. Results We revealed the ring structure of the mitochondrial genome, which spans 421,293 bp with 45.1% GC content and 56 annotated genes. Notably, we identified 514 repetitive sequences, including 123 Simple sequence repeats (SRs), 3 Tndem sequence repeats (TSRs), and 388 Dispersed sequence repeats (DSRs). We identified 79 out of the 388 DSRs as potentially involved in homologous recombination. We identified five forward repeats and four palindromic repeats that facilitate homologous recombination and induce alterations in the mitochondrial genome structure. We corroborated this finding via polymerase chain reaction (PCR). Furthermore, we identified chloroplast-derived sequence fragments within the mitochondrial genome, offering novel insights into the evolutionary history of plant mitochondrial genomes. We predicted 460 potential RNA editing sites, primarily involving cytosine-to-uracil transitions. This study reveals the complexity of repetitive sequence-mediated homologous recombination in the mitochondrial genome of G. glabra and provides new insights into its structure, function, and evolution. Conclusions These findings have important implications for conservation biology, population genetics, and evolutionary studies, underscoring the role of repetitive sequences in genome dynamics and highlighting the need for further research on mitochondrial genome evolution and function in plants.